Traction behaviour analysis on aged rubber using lab-scale environment simulated system - Amirul Hakim, Sufian (2023)
Tire aging is a critical factor that affects the performance and safety of vehicles on the road. Existing tire aging facilities are often large, complex, and expensive, limiting the understanding of tire aging and its impact on performance. A compact and efficient experimental device is needed to provide comprehensive knowledge about tire aging and its effects on tire performance. Road users are at risk of tire failure due to aging or damage, Thus, a better understanding of the rubber aging process and its relation to tire performance is crucial for developing effective strategies to prolong tire life and ensure road safety. The objectives of the study are to investigate rubber aging process under simulated environmental conditions in a lab-scale setup and to analyze traction behaviour of aged rubber materials and establish the relationship between aging and traction performance. In the study, a lab-scale setup, including an aging chamber and a traction tester, was designed to conduct experiments on rubber specimens. The study involved measuring the change in mechanical properties of tire rubber and comparing the contact characteristics of the tire rubber elastomer as it aged. In the first phase of the study, it is also observed that rubber hardness increased up to 20% as temperature and aging time increased up to 30 days. It is assumed that the phenomenon is due to oxidation and hardening of natural rubber through thermal aging. Additionally, the tensile test showed a decrease in stress as slow as 20% and elongation at break for rubber specimens with aging, as well as strain and stress at fracture decreased with increased aging duration and temperature. In the second phase of the study, traction test data showed a decline in average traction efficiency as lower as 20% as the rubber aged, possibly due to accelerated degradation processes, cumulative damage, or threshold behaviour. Furthermore, friction test results showed a decrease in average pulling force and friction coefficient as the rubber aged as slow as 20%. As summary, rubber aging negatively affects traction and frictional behaviour, impacting the performance and safety of tires. Understanding these relationships can help develop strategies to mitigate the negative impact of aging on rubber performance in various applications. In the suggested in future that, more advanced lab-scale setups could be developed for a better understanding of the aging process and its effects on tire performance, as well as exploring new materials or technologies to prolong tire life and enhance road safety are other areas of interest.